2021
DOI: 10.1590/0102-311x00014220
|View full text |Cite
|
Sign up to set email alerts
|

Descontinuidades contraceptivas no uso do contraceptivo hormonal oral, injetável e do preservativo masculino

Abstract: O objetivo foi estimar as taxas de descontinuidade total no uso do contraceptivo hormonal oral, injetável e do preservativo masculino, bem como verificar as taxas de interrupção por abandono e por troca para método mais eficaz e menos eficaz. Dados de 2.051 mulheres usuárias de unidades básicas de saúde de três capitais brasileiras foram coletados por meio do calendário contraceptivo. Os resultados mostraram que 24,5% das usuárias do contraceptivo hormonal oral, 33,5% das usuárias de contraceptivo hormonal inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 21 publications
0
3
0
6
Order By: Relevance
“…As for the lower use of condoms found in the female population, previous studies have also shown gender inequalities 12,13 . Although the male condom is the third most used contraceptive method by Brazilian women 3 , it has a high rate of discontinuity and is mainly replaced by hormonal contraceptives 35 , which suggests that the establishment of stable partnerships implies the adoption of other contraceptives and the abandonment of condoms. In the present study, the second most cited reason for not using condoms was the use of another method to prevent pregnancy, elucidating the lack of concern about the occurrence of STIs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As for the lower use of condoms found in the female population, previous studies have also shown gender inequalities 12,13 . Although the male condom is the third most used contraceptive method by Brazilian women 3 , it has a high rate of discontinuity and is mainly replaced by hormonal contraceptives 35 , which suggests that the establishment of stable partnerships implies the adoption of other contraceptives and the abandonment of condoms. In the present study, the second most cited reason for not using condoms was the use of another method to prevent pregnancy, elucidating the lack of concern about the occurrence of STIs.…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, some studies have indicated a low prevalence (10-11%) of dual protection among women of reproductive age 3,36 , which is in line with the worrying increase in STIs in recent years 9,10,21 . Another relevant fact is the reduction in condom use observed after the adoption of other contraceptives 32,35,37,38 , thus reiterating the greater exposure to STIs.…”
Section: Discussionmentioning
confidence: 99%
“…O início do uso de métodos contraceptivos ocorreu em torno do primeiro ao segundo mês e houve concentração do uso da pílula e da camisinha, que se manteve na segunda posição ao longo do tempo. Embora a fertilidade possa retornar até duas semanas após o abortamento (5) , é desaconselhável engravidar antes dos três meses, segundo o MS (5) , e até mesmo antes dos 6º mês pós-aborto, de acordo com a OMS (16) , por conta de maior possibilidade de repetição de abortamento, mas há ainda controvérsias na literatura internacional (17) . O fato das mulheres em período pós-abortamento terem usado majoritariamente métodos de curta duração, que acarretam maior risco de falhas, pode colocá-las em maior vulnerabilidade a uma nova gravidez antes do período recomendado.…”
Section: Discussionunclassified
“…Os tipos de descontinuidades variaram conforme o tipo de método contraceptivo utilizado, da mesma forma que observado na China (10) . A pílula foi o método que apresentou maior proporção de abandono tal e qual entre mulheres em geral de outros países (7), mas diferentemente do que já foi observado no Brasil (17) . A falha do método foi mais frequentemente observada entre as usuárias do preservativo masculino, assim como na Índia (9) , tendo em vista que se trata de um método de baixa eficácia (18) .…”
Section: Discussionunclassified
“…O cálculo e plano amostral utilizados na pesquisa mais ampla foram descritos por Borges et al 16 . Foram entrevistadas 2.051 mulheres, sendo 1.030 em São Paulo (2015), 508 em Aracaju (2016) e 513 em Cuiabá (2017).…”
Section: Metodologiaunclassified